BIMBINGAN PEMBERIAN KOMPRES HANGAT UNTUK MENGURANGI NYERI PERSALINAN - Darma, Ika Yulia; Zaimy, Silvi; Idaman, Meldafia; Moriyanda, Rury; Dasril, Oktariyani (Jurnal Abdimas Saintika, 2024)
Pain during labor accompanied by fear will slow down the labor process. Labor pain will cause hyperventilation, increase oxygen consumption, cause respiratory alkalosis, vasoconstriction of blood vessels in the uterus and acidosis in the fetus. Increasing non-adrenaline will reduce blood to the placenta and reduce uterine contractions, thereby interfering with the safety of the mother and fetus and the success of vaginal delivery. The aim of this service is to increase mothers' knowledge and skills in using warm compresses to treat pain in the first stage of labour. The aim of this service is to increase mothers' knowledge about preparing mothers for pain during labor using the warm compress technique. This activity was carried out from March 2024 to May 2024 at the Idaman Clinic, A.Md Keb, Padang City. Participants in this activity were 15 third trimester pregnant women. The form of activity is in the form of carrying out a pre-test, providing guidance on Warm Compresses, demonstrating the use of Warm Compresses and carrying out post-tests.  The results of this activity obtained an increase in mothers' knowledge and skills regarding the use of warm compresses. With this guidance activity and the use of warm compresses, it is hoped that efforts to reduce labor pain will be achieved so that the mother can feel comfortable and ready to face the birth process, which can have an impact on the smooth process of expelling the fetus.Keywords: labor pain, mother giving birth, Warm Compress